PENERAPAN BALANCED SCORE CARD PADA INDUSTRI MANUFAKTUR DI INDONESIA - Toto Kurniawan; Ririn Breliastiti (Jurnal Akuntansi Bisnis, 2017)
In order to face a competitive business environment, companies need to implement new strategies. Each flow measurement strategies need to be determined their level of success. So that a company needs to do a performance measurement in order to measure the level of success of the company. At this time, the financial performance indicators are considered no longer sufficient as a performance measurement system of the company, because it is not considered accurate in giving an assessment of the development of the company. In addition, it is not giving a clear picture about the focus and objectives of the company in the future. So we need a new paradigm in the measurement of the performance of companies in the information age today.This study aims to provide a discussion of the application of the Balanced Scorecard in the manufacturing industry in Indonesia. Given this example is expected that many companies in Indonesia which eventually attracted and can also take benefit. Researchers establish a manufacturing company as a research subject with the consideration that the manufacturing company has the scope of the most complex operations when compared with service companies and trade. Research on the application of balanced scorecard will be conducted in three selected manufacturing companies, namely PT Cahaya Harapan Satya Printing, CV Global Mandiri and PT Tanindo Sukses Makmur.The three companies have a Balanced Scorecard approach is a bit different, but still using the same four perspectives. Determination of the weight and the score is determined by the company taking into account the targets to be achieved for each perspective. The indicators used for each perspective also vary, depending on the target to be achieved, and the types of indicators can also vary. The three companies produce varying value Balanced Scorecard. For PT Cahaya Harapan Satya CV Printing and Global Mandiri has demonstrated good performance, but for PT Sukses Makmur Tanindo has not shown good performance. For PT Cahaya Harapan Satya CV Printing and Global Mandiri, this performance can be maintained. As for PT Sukses Makmur Tanindo performance should soon be upgraded to the condition with the category A, which is healthy.Keywords: Balanced Scorecard, manufacture, key performance indicator